Between Riga and Penang. Citizenship and Recognition of Cultural Difference in Latvia and Malaysia - Giordano, Christian (Sociologija. Mintis ir veiksmas, 2003)
Citizenship is undoubtedly one of the most fundamental concrete abstractions produced by philosophers and jurists. It is particularly interesting for sociologists and anthropologists as a phenomenon that structures collective representations and social relations amongst individuals and groups. In other words, social science is concerned with citizenship mainly as an imagined construction that essentializes in social life. Though not a complete survey, we would like to present some major sociological aspects of citizenship, aside from the philosophical or juridical ones.In the article I will compare by contrast two almost antithetical models of citizenship and analyze how two different concrete abstractions influence social life. I have chosen Latvia and Malaysia, where I am still directing two field studies particularly in two cities: Riga and Penang. My choice has a pragmatic reason. After its second independence, Latvia has introduced a model of citizenship in 1991, following the Staatsnation doctrine that tends to stamp out any form of cultural difference within its national territory. Malaysia, after the end of the British colonial domination in 1956, has given itself a model of multicultural citizenship, which is unmistakably based upon the celebration of difference amongst the country’s various ethnic components.
Keywords: citizenship; ethnicity; culture; essentialism; Latvia; Malaysia